The Role of Integrated Healthcare Center For Adolescents In Increasing Knowledge And Minimizing Health Risks In The Younger Generation - Muchamad Arif Al Ardha; Syamsuryanita Syamsuryanita; Nurul Ikawati; Nelli Roza; Johansen Hutajulu (Sean Institute, 2023)
Young people have a high level of health risk as they are undergoing rapid physical and mental changes. Therefore, it is crucial for young people to get accurate information and understanding about health. Adolescent integrated healthcare centers play a critical role in assisting youth in obtaining the necessary health information and knowledge and reducing youth health risks. Adolescents can get accurate health information and knowledge through health education programs and other services provided by integrated healthcare centers, which also serve to reduce adolescent health risks. Adolescent Posyandu can benefit most from this study's advice about how to increase their knowledge and understanding of health risks. Despite the fact that a comprehensive information-dissemination plan is required, young people must be made aware of the facilities and services offered by an integrated healthcare center for adolescents in order to draw them in for health-related consultations. Government and community support are crucial for bolstering and enhancing the services offered by an integrated healthcare center for adolescents.